2015
DOI: 10.1094/phyto-10-14-0264-r
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Conditions Affect Botrytis cinerea Infection of Mature Grape Berries More Than the Strain or Transposon Genotype

Abstract: Effects of environment, Botrytis cinerea strain, and their interaction on the infection of mature grape berries were investigated. The combined effect of temperature (T) of 15, 20, 25, and 30°C and relative humidity (RH) of 65, 80, 90, and 100% was studied by inoculating berries with mycelium plugs. Regardless of the T, no disease occurred at 65% RH, and both disease incidence and severity increased with increasing RH. The combined effect of T (5 to 30°C) and wetness duration (WD) of 3, 6, 12, 24, and 36 h was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
66
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(68 citation statements)
references
References 50 publications
(72 reference statements)
2
66
0
Order By: Relevance
“…Actually, B. cinerea incidence is favored by high humidity and long wetness duration. 26 Additionally, in the present study climatic conditions could be considered more favorable for C. sake CPA-1 survival and efficacy than in other growing seasons (2009 and 2010) in the same experimental field when BCA efficacy was significantly higher with coating additives. 9,27 Despite the mean averages of temperature and RH being very similar, during 2009 and 2010, accumulated rainfall was 28.0 mm and 30.2 mm, respectively, whereas during 2015 and 2016, accumulated rainfall raised to 56 mm and 34 mm, respectively.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Actually, B. cinerea incidence is favored by high humidity and long wetness duration. 26 Additionally, in the present study climatic conditions could be considered more favorable for C. sake CPA-1 survival and efficacy than in other growing seasons (2009 and 2010) in the same experimental field when BCA efficacy was significantly higher with coating additives. 9,27 Despite the mean averages of temperature and RH being very similar, during 2009 and 2010, accumulated rainfall was 28.0 mm and 30.2 mm, respectively, whereas during 2015 and 2016, accumulated rainfall raised to 56 mm and 34 mm, respectively.…”
Section: Discussionmentioning
confidence: 55%
“…Incidence differences between the two seasons were possibly caused by climatic conditions, mainly due to accumulated rainfall, which was scarce in 2016 and principally occurred at the end of the season. Actually, B. cinerea incidence is favored by high humidity and long wetness duration . Additionally, in the present study climatic conditions could be considered more favorable for C. sake CPA‐1 survival and efficacy than in other growing seasons (2009 and 2010) in the same experimental field when BCA efficacy was significantly higher with coating additives .…”
Section: Discussionmentioning
confidence: 61%
“…Therefore, new control strategies that allow growers to reduce the application of pesticides should be developed based on the principles of integrated pest management (IPM) (International Organization for Biological and Integrated Control 2009). Climatic and microclimatic conditions, specifically temperature and humidity, are key factors for B. cinerea infection, notably in grapevine (Savage and Sall 1984, Thomas et al 1988, English et al 1989, Nair and Allen 1993, Broome et al 1995, Fermaud et al 2001, Valdés-Gómez et al 2008, Ciliberti et al 2016. This development depends on three major factors: (i) climatic and microclimatic conditions; (ii) the presence/amount and characteristics of the pathogen inoculum; and (iii) the susceptibility of the host, that is grapevine.…”
Section: Introductionmentioning
confidence: 99%
“…This development depends on three major factors: (i) climatic and microclimatic conditions; (ii) the presence/amount and characteristics of the pathogen inoculum; and (iii) the susceptibility of the host, that is grapevine. Climatic and microclimatic conditions, specifically temperature and humidity, are key factors for B. cinerea infection, notably in grapevine (Savage and Sall 1984, Thomas et al 1988, English et al 1989, Nair and Allen 1993, Broome et al 1995, Fermaud et al 2001, Valdés-Gómez et al 2008, Ciliberti et al 2016. Favourable climatic conditions include a temperature between 15 and 25 C and a wetness duration between 12 and 24 h (Thomas et al 1988).…”
Section: Introductionmentioning
confidence: 99%
“…At 30 °C, conidia are not produced, and conidial germination is arrested. At optimal temperatures, germination occurs within 3 h. Numerous studies have demonstrated that free moisture is essential for conidial germination and berry infection (Broome et al, 1995;Ciliberti et al, 2015b;Coertze and Holz, 2002;Nair and Allen, 1993;Steel et al, 2011;Thomas et al, 1988).…”
Section: Environmental Factorsmentioning
confidence: 99%